Petani, Lahan dan Pembangunan: Dampak Alih Fungsi Lahan terhadap Kehidupan Ekonomi Petani - Tari Purwanti (Umbara, 2018)
This study aims to describe how paddy lands convertion from agricultural to non-agricultural could impacts to the farmers household economy in order to fulfill their needs of subsistence. The research describes in detail how the impact of lands convertion to the economy of farmers. This research used qualitative method with in-depth interview and participant observation to obtain in-depth data. The study was conducted in RW 05 Dusun Sukanegla, Hegarmanah Village in Jatinangor from June until September 2016. The result of research shows that most of the farmers got an increase in income after the land convertion while the other experienced a decrease in income by a range of factors. The impact of construction in economic area is not always mean negative for farmers, but also can be positive if farmers are able to see the opportunity income from non-agricultural sector and less dependent on aid.